Delphinium blues - Morgan, Stevie (Hodder & Stoughton, 1999)
When Jess is dumped by her husband of 15 years for a red-haired 20-something, she is left with two grief-stricken children, a vast mortgage and nothing on her CV but cake crumbs. But, starting with painting her bedroom pink, she reinvents herself to discover there is life after divorce.